Antioxidant, antityrosinase and antibacterial activities of fruit peel extracts - Musika, S.; Pokratok, N.; Pliankratoke, J.; Khongla, C.; Kupradit, C.; Ranok, A.; Mangkalanan, S. (International Journal of Agricultural Technology, 2021)
Total phenolic compounds, antioxidant, antityrosinase and antibacterial activities of ethanolic fruit peel extracts of six different fruits: cantaloupe, passion fruit, pineapple, dragon fruit, watermelon and raw mango were recorded. The results showed that the mango, Mangifera indica L. peel ethanolic extract (MIPE), contained high total phenolic compounds of 56.79 ± 1.86 mgGAE/g extract. MIPE possessed an ABTS radical scavenging activity and a ferric reducing activity of 594.21 ± 2.94 and 344.91 ± 17.15 mgTrolox/g extract, respectively. MIPE also inhibited radical scavenging activity with an IC50 value of 0.37 ± 0.01 mg/ml. All the six extracts had significantly less effective antityrosinase activitythan kojic acid. In addition, MIPE was able to inhibit Staphylococcus epidermidis with 6 strains and also inhibit Streptococcus pyogenes with 5 strains. The results suggested that mango could be promoted as a potential source of natural antioxidant and as an antimicrobial agent to apply in functional food, nutraceutical or cosmetic formulations